Phase, microstructure, thermochromic, and thermophysical analyses of hydrothermally synthesized W-doped VO2 nanopowder - Barra, Hamdi Muhyuddin; Chen, Soo Kien; Tamchek, Nizam; Talib, Zainal Abidin; Lee, Oon Jew; Tan, Kar Ban (Hindawi Limited, 2021)
Vanadium dioxide (VO2) has great potential as an intelligent architectural glazing system as it can control the amount of light, heat, and solar energy relative to the temperature in the environment. However, the applicability of VO2 for commercial use is yet to be realized because its phase transition temperature (τc) of ∼68°C is too high for use in buildings. A proven strategy to lower its τc is by elemental doping. Hence, in this study, hydrothermal synthesis of nanostructured VO2 was carried out with the introduction of tungsten (W) as a dopant. Furthermore, the effects of W doping on the structural, thermochromic, and thermophysical properties of VO2 were examined. Using X-ray diffraction (XRD), it was found that the addition of W atoms affected the VO2 lattice since the crystal structure of VO2 was changed from monoclinic to tetragonal rutile. Subsequently, this influenced the thermochromic behavior of the prepared VO2. Based on the differential scanning calorimetry (DSC), doping with tungsten resulted in a significant decrease in τc from 66.47°C to as low as 31.64°C. Moreover, W doping affected the thermophysical properties of the samples. Accordingly, an abrupt increase in the thermal conductivities of the doped samples was observed across the transition temperature.